Analysis of the Influence of Community Perceptions in Ambon on Sharia Fintech - Nurlette, Erlin D. P.; Nacikit, Muhammad R; Shalihah, Maratun; Maruapey, Muammar W; Yaman, Afdhal; Malawat, Fadli F; Hamizar, Arizal (Denisya Smart Consulting, 2024)
This research aims to determine the perception of the people of Ambon city regarding the existence of sharia fintech in Ambon city. The population in this research is the people of Ambon city. The research method used is a quantitative method. The sample taken was 100 respondents using a questionnaire distribution technique with a Likert scale. Hypothesis testing uses multiple linear analysis methods with SPSS version 26 tools. The results of this research show that 1) Partially (T test), the product, promotion, place and non-usury variables have a significant influence on the dependent variable